#1**+1 **

__First Question__

9x - 9y = -99x - 9y = -9

9x - 9y = -99x - 9y = -9 (cancel -9y)

9x = -99x = -9 | ÷ -9

-x = 11x = 1 | + x

0 = 12x = 1+x

If 12x = 0, then x = 0 but 1+x = 1+0 = 1 so 0 = 0 = 1 is not true. Hence there are no solutions

**Second Question**

= 11 + (**(-8x + 9y)** = 11 | -(- 8x + 9y) on all sides**- 8x + 9y)**

0 = 11 + 0 = 11

0 = 11 = 11

0 ≠ 11

No solutions

MWizard2k04
Mar 22, 2017

#2**+1 **

First question:

9x - 9y = -99x - 9y = -9

That implies: x - y = -11x - y = -1

x - y = -11x - y

x = -11x

1 = -11

That means you can't divide by x because you get a strange result..... That means x = 0.

0 - y = -1, y = 1.

Therefore \(x = 0, y= 1\)

Second question:

-8x + 9y = 11 - 8x + 9y = 11

Only know that you cannot subtract a number which is not 0 and then get the same results......

Therefore no solution.

MaxWong
Mar 22, 2017